2021
DOI: 10.1128/aac.01900-20
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Population Pharmacokinetics of and Acute Kidney Injury Due to Polymyxin B in Chinese Patients with or without Renal Insufficiency

Abstract: Despite excellent bactericidal effect, dosing adjustment of polymyxin B for patients with renal insufficiency and polymyxin B-related nephrotoxicity is still a major concern to clinicians. The aim of this study was to compare the population pharmacokinetic (PK) properties of polymyxin B in Chinese patients with different renal function and to investigate the relationship between PK parameters and polymyxin B related-acute kidney injury (AKI). A total of 37 patients with normal renal function (creatinine cleara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
43
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 36 publications
7
43
4
Order By: Relevance
“… 22 Furthermore, a PMB PPK study found that CL and Q values differed significantly in patients with normal and reduced renal function, whereas the variance and median AUC ss,24h changes remained within a 2-fold range in patients treated with a weight-based maintenance dose, a finding commonly accepted as the threshold justification for dosing adjustment. 18 , 31 Although dosing adjustment may not be necessary in patients with renal impairment, this strategy has been associated with increased toxicity rates in patients with decreased renal function, with over 50% of simulated AUC ss,24h being >100 mg∙h/L. 18 Moreover, weight-based maintenance doses have been associated with increased toxicity in higher-weight patients.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“… 22 Furthermore, a PMB PPK study found that CL and Q values differed significantly in patients with normal and reduced renal function, whereas the variance and median AUC ss,24h changes remained within a 2-fold range in patients treated with a weight-based maintenance dose, a finding commonly accepted as the threshold justification for dosing adjustment. 18 , 31 Although dosing adjustment may not be necessary in patients with renal impairment, this strategy has been associated with increased toxicity rates in patients with decreased renal function, with over 50% of simulated AUC ss,24h being >100 mg∙h/L. 18 Moreover, weight-based maintenance doses have been associated with increased toxicity in higher-weight patients.…”
Section: Discussionmentioning
confidence: 99%
“… 18 , 31 Although dosing adjustment may not be necessary in patients with renal impairment, this strategy has been associated with increased toxicity rates in patients with decreased renal function, with over 50% of simulated AUC ss,24h being >100 mg∙h/L. 18 Moreover, weight-based maintenance doses have been associated with increased toxicity in higher-weight patients. 32 , 33 In the present study, a fixed maintenance dose of 60 mg q12h provided sufficient antimicrobial coverage against carbapenem-resistant Gram-negative organisms in patients with renal impairment, along with a relative low risk of toxicity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations